கலித்தொகையில் தொன்மக்கூறுகள் / Myth in Kalithogail - முனைவர் த.க. ஜாஸ்மின் சுதா / Dr. T.K. Jasmin Sudha (Chenkaantal)
Epics, legends and myths were first spoken orally and later found their place in literature in written form. Sangam poets used these verses as metaphors in their hymns. In Sangam literature, the Eight Books (Ettuthogai) and the ten-fold books (Pattupattu) reveal the life, culture, and culture of that time. To express them, the poets of that time used stories based on mythology, epics and traditions as parables. Through those parables we can feel the reflection of that time. This paper discloses the mythological elements present in the chosen sources. Since Sangam literature has a wide range, only the mythological elements found in some specific songs in “Kalithogai” have been analyzed in this article. The concepts of myth and their use in mythical literature are explored in detail with the help of sources.